Quercus laevis, Turkey Oak - Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana (EDIS)
This document provides a comprehensive overview of Quercus laevis, commonly known as Turkey Oak. It details the tree’s taxonomy, physical characteristics, habitat, and uses. The article highlights its distinctive turkey-foot-shaped leaves, its adaptability to xeric environments, and its role in providing food for wildlife. Additionally, it discusses the tree’s allergenic properties, storm tolerance, and limited commercial value, primarily as firewood. The document also emphasizes Turkey Oak’s horticultural benefits, particularly its drought tolerance and aesthetic appeal in landscapes. Original publication date May 2010.